THE INFLUENCE OF CULTURAL CONTEXT ON CONTEMPORARY FASHION DESIGN: THE TRANSFORMATION OF AESTHETICS IN THE GLOBAL SPACE - Корнєва, Тетяна (SWorldJournal, 2026)
The relevance of the study is determined by the growing influence of globalization processes in the fashion industry, which transform local cultural traditions and raise the question of preserving cultural identity in the context of the dominance of unifi